Tonsil mesenchymal stem cells-derived exosomes differentially effect the cell proliferation depending on different temperature conditions - Yüce, Melek; Şişli, İlayda and Çiftcioğlu, Ezgi and Albayrak, Esra and Kırbaş, Oğuz Kaan and Taşlı, Pakize Neslihan and Özdemir, Doğukan and Şahin, Fikrettin (The European Research Journal, 2024)
Objectives: Exosomes are suggested as cellular components with therapeutic and prognostic potential in various disease therapies and exhibit different secretion profiles under cellular stress. Mesenchymal stem cells (MSCs), which play an important role in regenerative medicine, are particularly rich in exosome release compared to other cell types. In this context, the effect of exosomes obtained from palatine tonsil tissue derived MSCs (T-MSC) under different temperature conditions on cell proliferation were investigated in vitro on cancer and healthy cells. Methods: Exosomes were isolated from MSCs under normal temperature conditions and heat stress, and their concentrations and size distribution were determined by nanoparticle tracking analysis. The effects of exosomes obtained under different conditions on cell proliferation in healthy and cancer cell lines were determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, while their effects on cell migration were evaluated by wound healing assay. Results: Exosomes obtained under normal temperature conditions and heat stress did not exhibit very different properties in terms of size distribution, but particles were obtained at approximately 2 times higher concentrations under normal temperature conditions. They showed different effects in terms of cell proliferation. Exosomes obtained under normal conditions significantly increased cell proliferation in keratinocyte cells depending on the concentration. However, exosomes obtained in cancer cells, especially after heat stress, significantly inhibited cell proliferation. Conclusions: While exosomes obtained under heat stress come to the forefront in inhibiting cell proliferation in cancer cells, exosomes obtained under normal conditions stand out as effective in wound healing by stimulating increased normal cell proliferation.